Respuesta :
Answer:
x= -4
Step-by-step explanation:
Step 1: Simplify
2x-3+3x=-23 turns into
5x-3=-21 -- combined like terms
Step 2: Start Solving
5x-3 = -23
+3 +3 -- Getting x alone by adding 3 to cancel it out
5x = -20
/5 /5 -- getting x alone by dividing by 5 to again cancel it out
Step 3: The answer
x = -4
Answere:
x=-4
Step-by-step explanation:
well, if you have the equation 2x-3+3x=-23, The first thing you wanna do is add up the X's so 2x+3x=5x, and then you put the 5x in the equation instead of 2x+3x:
-3+5x=-23
Then you since you have a -3, you should add 3 on BOTH sides of the equal sighn. And when you add 3 and -23 you get -20, so the new equation is:
5x=-20, from there you can tell X=-4
Tell me if you have any questions, and im sorry if the explaination is not thta good, I explain stuff better when i am face to face with someone, Have a good day!